Wheat bran components modulate intestinal bacteria and gene expression of barrier function relevant proteins in a piglet model. (2nd January 2017) - Chen, Hong; Chen, Daiwen; Qin, Wen; Liu, Yuntao; Che, Lianqiang; Huang, Zhiqing; Luo, Yuheng; Zhang, Qing; Lin, Derong; Liu, Yaowen; Han, Guoquan; DeSmet, Stefaan; et al.
Abstract: The objective of this study was to determine the impact of wheat bran and its main polysaccharides on intestinal bacteria and gene expression of intestinal barrier function relevant proteins. Thirty freshly weaned male piglets were assigned randomly to five dietary treatment groups with six piglets per group. Accordingly, five synthetic diets including a basal control diet without fiber components (CON), wheat bran diet (10% wheat bran, WB), arabinoxylan diet (AX), cellulose diet (CEL) and combined diet of arabinoxylan and cellulose (CB) were studied. The piglets were fed ad libitum for 30 d. Lower Escherichia coli (E. coli) populations in WB group and higher probiotic ( Lactobacillus and Bifidobacterium) populations in groups fed diets containing arabinoxylan (WB, AX and CB) were observed and compared with CON group. Compared with CON group, the gene expressions of cystic fibrosis transmembrane conductance regulator (CFTR), calcium-activated chloride channel regulator 1 (CLCA1) and voltage-gated chloride channel 2 (CIC2) were suppressed in the WB group. And wheat bran down-regulated gene expression of pro-inflammation (TNF-α, IL-1β, IL-6) and TLRs/MyD88/NF-κB pathway compared with CON group. In conclusion, wheat bran and its main polysaccharides could change intestinal microflora and down-regulate the gene expression of intestinal barrier function relevant proteins in the distal small intestinal mucosa.